TRANSFORMASI PEMBELAJARAN SAINS DI SEKOLAH DASAR MELALUI PENDEKATAN INKUIRI, PBL, PjBL, DAN STEM DALAM MENUMBUHKAN KETERAMPILAN ABAD KE-21 - Ena Suma Indrawati; Meri Yessari; Bismi Afia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
thinking, critical attitudes, and life skills from an early age. However, science instruction in elementary education is still often dominated by conventional approaches focused on memorization of concepts. This article aims to comprehensively examine the transformation of science learning through innovative learning approaches and models, namely inquiry learning, Problem-Based Learning (PBL), Project-Based Learning (PjBL), cooperative learning, and the STEM approach, in fostering 21st-century skills. This study employs a literature review method by analyzing textbooks and relevant scientific sources related to elementary science education. The results indicate that innovative learning models effectively enhance students’ critical thinking, creativity, collaboration, and communication skills. Therefore, transforming science learning through innovative approaches is essential to improving learning quality and aligning elementary education with the demands of the 21st century